Layanan Bimbingan Kelompok untuk Pencegahan Paham Radikalisme di Perguruan Tinggi - Intan Sari (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2019)
During the transition of the identity crisis, young people are likely to experience cognitive opening that makes them vulnerable to new, more radical ideas. Seeing this condition, Islamic Higher Education has an important role in preventing radicalism in students at Islamic Higher Education. Students need assistance and understanding so that they do not easily fall prey to radical movements, including through group counseling activities. In group guidance activities, group activities and dynamics must be realized to discuss various things that are useful for the development and problem solving of individuals (students) who become service participants. Group guidance activity aims to add insight into the knowledge skills, values , and attitudes of group members regarding the prevention of radicalism. This paper used a study of literature method, it is collecting various reading materials and information related to the phenomena and studies discussed. Based on the studies that have been carried out, it can be concluded that through the dynamics of groups that are actively predicted, it can increase the activity and participation of group members (students) in analyzing and understanding Islamic ideas that areÂ rahmatan lilalamin, tolerance, not fanatical towards certain groups, and strengthening nationalism.